Juridical Analysis of Legal Responsibility for The Dissemination of Deepfake Content on Social Media - Harri Prasetyo Rachmatullah (Jurnal Indonesia Sosial Sains, 2026)
The development of Artificial Intelligence technology, particularly Deepfake, has created new legal challenges due to the dissemination of manipulative content on social media that potentially harms individuals and the public. This phenomenon poses serious difficulties for the Indonesian legal system in ensuring legal protection and certainty. This study aims to analyze the existing legal framework and forms of legal liability for the distribution of Deepfake content in Indonesia. The research employs a normative legal method using statutory and literature-based approaches. The findings indicate that although the ITE Law, Personal Data Protection Law, and civil law may be applied, significant legal gaps remain, necessitating the establishment of specific regulations governing Deepfake technology.